(untitled) (Archives of Clinical Psychiatry, 2010)
BACKGROUND: Childhood and adolescence are relevant periods for the brain maturation process. Experiences in early life have an important influence on adults patterns of behavior. OBJECTIVE: To analyze what have been published in the last 20 years about neuropsychological and neuroimaging, associated with occurrence of various forms of emotional stress in childhood and adolescence. METHODS: Literature review of the Medline/PubMed database with the terms related to neuropsychology, neuroimaging, abandonment experience, domestic violence, physical and sexual abuse and neglect. RESULTS: 607 articles were found but only 19 fit with the proposed subject and were selected. Despite the differences between the studies, there is evidence that groups with experience of early emotional stress show losses in neurocognitive functions such as attention, intelligence, language, executive functions, and decision-making, as well as changes in hippocampus, corpus callosum prefrontal cortex, and anterior cingulate cortex. The occurrence of psychiatric disorders and behavioral disorders were also relevant in these individuals. DISCUSSION: Considering many negative consequences that early stress can cause in neuropsychological and mental development, there is a need for more research on the topic in order to develop specific strategies for diagnosis and treatment, besides the implementation of public policies for violence prevention in childhood and adolescence, especially in developing countries.